Development of new OCDMA code - Nor Ilyana Osman (Universiti Malaysia Perlis, 2008)
Nowadays, communication is very important at any place, time and situation. The transmission of signal can be in wireless or cable (especially fiber optic that has more advantages than others cable for a long distance). Furthermore, there are three type of division multiple accesses that use in communication systems which are Time Division Multiple Access (TDMA), Wavelength Division Multiple Access (WDMA) and Code Division Multiple Access (CDMA). But, CDMA has been recognized to provide efficiency, security, and multi-access benefits in wireless communications. This has triggered interest in providing similar advantages for optical communication systems. Optical code division multiple access (OCDMA) is an interesting subject of research because of its potential to support asynchronous, burst communications. The performance of any OCDMA system strongly depends on the codes properties. The application of codes had been develop need to be improved to get the good transmission performance in OCDMA system.